Placental Cadmium Levels Are Associated with Increased Preeclampsia Risk - Laine, Jessica E. (PLoS One, 2015)
Environmental exposure to heavy metals is a potentially modifiable risk factor for preeclampsia (PE). Toxicologically, there are known interactions between the toxic metal cadmium (Cd) and essential metals such as selenium (Se) and zinc (Zn), as these metals can protect against the toxicity of Cd. As they relate to preeclampsia, the interaction between Cd and these essential metals is unknown. The aims of the present study were to measure placental levels of Cd, Se, and Zn in a cohort of 172 pregnant women from across the southeast US and to examine associations of metals levels with the odds of PE in a nested case-control design. Logistic regressions were performed to assess odds ratios (OR) for PE with exposure to Cd controlling for confounders, as well as interactive models with Se or Zn. The mean placental Cd level was 3.6 ng/g, ranging from 0.52 to 14.5 ng/g. There was an increased odds ratio for PE in relationship to placental levels of Cd (OR = 1.5; 95% CI: 1.1–2.2). The Cd-associated OR for PE increased when analyzed in relationship to lower placental Se levels (OR = 2.0; 95% CI: 1.1–3.5) and decreased with higher placental Se levels (OR = 0.98; 95% CI: 0.5–1.9). Similarly, under conditions of lower placental Zn, the Cd-associated OR for PE was elevated (OR = 1.8; 95% CI: 0.8–3.9), whereas with higher placental Zn it was reduced (OR = 1.3; 95% CI: 0.8–2.0). Data from this pilot study suggest that essential metals may play an important role in reducing the odds of Cd-associated preeclampsia and that replication in a larger cohort is warranted.